Technique for Coherent Segmentation of Image and Applications - Asatryan, David G.; Sazhumyan, Grigor S.; Shahverdyan, Hayk S. (Mathematical Problems of Computer Science, 2021)
In this paper we describe a software tool created according to an algorithm, which was proposed earlier by authors for coherent and multi-scale segmentation of an image. The algorithm is based on the finding of all connected segments, the pixels of which belong to the same, determined beforehand and adjustable levels of intensity. Various modes of operation of the software are described, which allows to separate segments or to carry out full segmentation, as well as to transfer the parameters of one segment to others and to estimate quality of the carried out segmentation. It is shown that the segmentation procedure is able to determine simultaneously edges and contours in the image. The results of the computing experiments showing efficiency of developed system are given.